Imagining Accessibility: Theorizing Disability in Disabled People Destroy Science Fiction - Matthew Holder (Disability Studies Quarterly, 2020)
With its emphasis on futurity, its close association with scientific plausibility, and its dedicated interrogation of contemporary ideologies, science fiction stands as a genre ripe with possibilities for disability studies. Many scholars have used the genre and its texts as platforms from which to either condemn or laud representations of disability within a field explicitly concerned with a society's future. My essay contributes to this discussion by foregrounding a science fiction text to theorize what a disabled future looks like. I take as my primary text a selection of short fiction from Uncanny Magazine, an online magazine that published a disability-themed issue Disabled People Destroy Science Fiction in 2018. The stories contained are penned exclusively by authors that identify as disabled; their visions of a disabled future, then, emerge from the contemporary experience of the disabled community. In addition to centering themselves in the discourse, these writers envision a disabled future as one that emphasizes community and frequently critiques and interrogates the costs, emotional and physical, inherent in the medical model of disability, announcing that a truly disabled future is one that features rather than erases the disabled mind and body. Running with the banner of destroying SF, these writers challenge the conventional, harmful tropes that SF has perpetuated and erects in its place an inclusive, intersectional, and disabled future.
Keywords: theory; science fiction; short fiction; Siebers; Schalk